EPID-24. OBESITY IN MALES WITH MENINGIOMA: A U.S. POPULATION-BASED STUDY. (9th November 2020) - Shahin, Maryam; Rae, Ali; Ramos, Christian Lopez; Bagley, Jacob; Bowden, Stephen; Bullis, Carli; Cetas, Justin; Han, Seunggu
Abstract: BACKGROUND: The female predominance of meningiomas may reflect a hormonal influence on tumorigenesis. Obesity alters steroid synthesis and chronically exposes men to hyperestrogenemia. OBJECTIVE: Identify differences in males undergoing craniotomy for meningioma compared to other tumors or aneurysms. METHODS: The National Surgical Quality Improvement Program was retrospectively queried from 2013–2018 for cases of craniotomy for resection of meningioma, other tumor, and aneurysm by CPT code in male patients and confirmed with postoperative ICD-10 code. Height and weight data were used to create body mass index (BMI): underweight (< 18.5), normal (18.5 to< 25), overweight (25 to< 30), class I obesity (30 to< 35), class II obesity (35 to< 40), and class III obesity (40+). RESULTS: We identified 2, 458 males who underwent craniotomy for meningioma, 9, 889 for other tumor, and 386 for aneurysm. Using multivariable logistic regression, age (OR 1.01 per year, 95% CI 1.01-1.01, p< 0.001), diabetes mellitus (OR 1.32, 95% CI 1.17–1.48, p< 0.001), and increasing BMI (overweight: OR 1.55, 95% CI 1.36–1.76, p< 0.001; class I: OR 2.00, 95% CI 1.75–2.30, p< 0.0001; class II: OR 2.05, 95% CI 1.24–1.76, p< 0.001; class III: OR 1.47, 95% CI 1.24–1.76, p< 0.0001) were significantly and independently associated with craniotomy for meningioma compared to other tumor or aneurysm. For other tumor, higher BMI was associated with lower likelihood (overweight: OR 0.70, 95% CI 0.62–0.79, p< 0.001; class I: OR 0.55, 95% CI 0.49–0.63, p< 0.001; class II: OR 0.52, 95% CI 0.44–0.62, p< 0.001; class III: OR 0.74, 95% CI 0.63–0.87, p< 0.001). For aneurysm, there was no significant difference (overweight p=0.70; class I p=0.65; class II p=0.76; class III p=0.57). CONCLUSIONS: BMI independently predicts having craniotomy for meningioma when compared to other tumor or aneurysm amongst US male patients.